PERBANDINGAN PUTUSAN PN TENTANG TINDAK PIDANA NARKOTIKA DENGAN TINDAK PIDANA PENCURIAN YANG DILAKUKAN ANAK (Studi Kasus Putusan PN No. 66/Pid.Sus/2014/PN.Skt dan Putusan PN No. 01/Pid.Sus/2014/PN.Skt) - ROKHADI, ROKHADI (Dinamika Hukum, 2015)
This study aims to determine the differences in legal protection and consideration of the judge in deciding the case narcotic and theft committed by children ( PN Decision Case Study No. 66 / Pid.Sus / 2014 / PN PN.Skt and Decision No. 01 / Pid.Sus /2014/PN.Skt ). This research method using a normative approach to the form of qualitative research . The type of data used in the writing of this law is the primary data . The primary data source used is the result of interviews with those who know about the problem under study . Analysis of the data obtained is done by means of qualitative analysis. Based on the analysis and discussion of the results it can be concluded that the legal protection of children who commit criminal offenses and theft of narcotics can be seen from the Decision of Judge impose imprisonment for the crime of child accused of drug cases and cases of theft in accordance with Article 71 of Law No. 11 of 2012 on crime Juvenile Justice System ) which states that the criminal child over the age of 15 years may be subject to criminal prison . Consideration of the judge in deciding criminal cases Narcotics ( PN Decision Case Study No. 66 / Pid.Sus / 2014 / PN.Skt ) , the judge considered the fourth indictment violated the provisions of Article 132 paragraph ( 1 ) as referred to in Article 111 paragraph 2 of Law Decree No. 35 of 2009 on Narcotics . Meanwhile, the judge consideration in deciding criminal cases Theft ( PN Decision Case Study No. 01 / Pid.Sus / 2014 / PN.Skt ) judges consider the provisions of Article 363 paragraph ( 1 ) to 4 Code of Criminal Law . Keywords : Crime Narcotics , Theft Crime , Crime Child Actors